Estudo do efeito do beta-cariofileno no modelo de esquizofrenia induzida por cetamina em camundongos - Clemente, Dino Cesar da Silva (2019)
Schizophrenia is a disorder characterized by the presence of negative and positive symptoms, who is current pharmacotherapy has been palliative and limited effective ness. Thus, researches related to the development of drugs useful in the treatment of this disorder are of interest. In this context, phytocannabinoids may be a potential source for the modulation of symptoms of schizophrenia. Beta-caryophyllene (BCF) has CB2 agonist action and has antipsychotic activity. CB2 receptors have been triggered in a controlled manner by G protein-coupled receptors as active receptor cells are capable of activating therapeutic plaques, with potential to relieve symptoms, without collateral variations to the central nervous system. The present study investigated the behavior al and neurochemical alterations of animals submitted to the model similar to ketamine-induced schizophrenia (20 mg/kg, i.p.) and possible reversion with beta-caryophyllene was observed. In reversal treatment, adult male Swiss mice received either saline or ketamine for 14 days. On the 8th to 14th day they also received beta-caryophyllene (10 or 50 mg/kg, p.o.) and olanzapine (2.5 mg-kg, i.p.) used as standard antipsychotic, 30 minutes after saline or ketamine. Behavior al tests to evaluate positive symptoms, locomotor activity (open field) and pre-pulse inhibition (PPI), negative symptoms (social interaction) and cognitive (labyrinth in Y) were performed. The parameters of oxidative stress, reduced glutathione (GSH), thiobarbituric acid reactive substances (TBARS) and nitrite were measured in the prefrontal cortex, hippocampus and striatum. The molecular fittings between BCF and peroxisome proliferator activated receptor alpha -PPARα, BCF and receiver CB2, BCF enzyme fatty acid amide hydrolase - FAAH and cannabidiol- CBD receiver PPARα, CBD and receiver CB2, CBD receiver FAAH receptor were also carried out. BCF reversed changes induced by ketamine demonstrated in behavior al parameters andoxidative markers, thatis, reduction of TBARS content and decrease of nitrite levels in, hippocampus. In the study of molecular docking BCF showed chemical, spatial and energetic compatibility with CB2 receptor, FAAH enzyme and PPARα receptor. Our results point to the potential antipsychotic effect of BCF in the reversal of the schizophrenic-like disorder and suggest that its therapeutic efficacy withn neuroprotective action is significant for its antioxidant, nitrergic activities, besides displaying interaction with CB2 receiver.